SIPUJO: OSCE Examination Assessment Application for Lecturer of the Faculty of Medicine, State University of Surabaya - Ramadhani, Puput Ayu; Fanani, Muhammad Zaki Jauhar; Mislica, Anita; Masturo, Muhaiyinatun; Pratama, Anugrahani Sabillia Noor (International Conference on Biomedical and Sports Medicine, 2025)
Assessment in Objective Structured Clinical Examination (OSCE) is a crucial aspect in medical education to measure students’ clinical competence. The Faculty of Medicine, State University of Surabaya (UNESA) currently still uses a manual assessment system based on excel format that is prone to various problems, such as ineffectiveness in data management, recording errors, and limitations in analyzing exam results. To face these challenges, this study aims to develop SIPUJO (OSCE Examination Assessment Application), a digital-based system designed to improve efficiency, accuracy, and transparency in the OSCE examination assessment process. SIPUJO was developed as a web-based application that allows lecturers to enter the assessment point real-time and directly via electronic devices. The system will analyze automatically and easily accessed by academic staff, thus accelerating the process of recapitulation and reporting of exam results. This application offers convenience in data management, increases assessment accuracy, and supports transparency in the evaluation of exam results.